Tingkat integrasi perencanaan dana alokasi khusus fisik dan non-fisik dalam mendukung reformasi struktural daerah - Andi Pambudi; Rendy Riyanto (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
The phenomenon of fiscal decentralization in Indonesia highlights the importance of aligning national and regional policies, particularly in implementing the Special Allocation Fund (DAK) as a fiscal instrument that bridges the National Government Work Plan (RKP) and Regional Government Work Plans (RKPD). However, there remains a research gap concerning the extent to which Physical and Non-Physical DAK programs are integrated within regional planning documents under a thematic, holistic, integrative, and spatial framework. The urgency of this study lies in ensuring that fiscal transfers from the central government are not only absorbed but also effectively targeted to support post-pandemic economic recovery and structural reform. This research aims to analyze the degree of DAK integration within the RKPD of 34 provinces using a document-based content analysis and tagging of DAK activity menus. The results reveal that tourism and agriculture sectors show high integration in non-physical activities (70% and 65%), while the environmental sector remains the lowest (physical 43%, non-physical 12%). Spatial disparities persist between western and eastern regions of Indonesia. Strategic recommendations include strengthening the digital tagging mechanism through KRISNA–SIPD integration, enhancing regional capacity in applying the Thematic, Holistic, Integrative, and Spatial (THIS) approach, and adopting evidence-based planning to improve the effectiveness of DAK in achieving sustainable regional development.